2016
DOI: 10.21014/acta_imeko.v5i4.415
|View full text |Cite
|
Sign up to set email alerts
|

The application of texture features to quality control of metal surfaces

Abstract: Quality assessment is an important step in production processes of metal parts. This step is required in order to check whether surface quality meets the requirements. Progress in the field of computing technologies and computer vision gives the possibility of visual surface quality control with industrial cameras and image processing methods. Authors of different papers proposed various texture feature algorithms which are suitable for different fields of images processing. In this research 27 texture feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Texture analysis in particular has recently been studied by a number of authors. For example, Trambitckii et al [30] found a strong correlation between surface roughness and image features extracted with various algorithms.…”
Section: Metal Surface Qualitymentioning
confidence: 99%
“…Texture analysis in particular has recently been studied by a number of authors. For example, Trambitckii et al [30] found a strong correlation between surface roughness and image features extracted with various algorithms.…”
Section: Metal Surface Qualitymentioning
confidence: 99%